Institutional Convergence of Synergistic Strengths for Developing Women Agripreneurs - Rashmi Singh , M. S. Nain , J. P. Sharma , J. R. Mishra , Anjani Kumar and R. R. Burman, (Indian Journal of Extension Education, 2014)
Aparadigm shift from agriculture being as a way of life for managing farm commercially on lines of an agribusiness is anessential pathway to revitalize Indian agriculture and to make farming a more attractive and profitable venture.Agripreneurship have the potential to contribute to a range of social and economic development. Agripreneurship haspotential to generate growth, diversifying income, providing widespread employment and entrepreneurial opportunitiesin rural areas, though is an intricate process of mobilizing, stimulating needs, inculcating entrepreneurial competencies,facilitating linkages with other agencies, mentoring and hand holding. The study was conducted in Hapur district of UttarPradesh where three villages Lalpur, Shyampur and Kania-kalianpur were selected purposively being predominantlyengaged in agriculture and having scope of agripreneurship development due to their proximity to National capital ofDelhi. Ninety farm women, 30 each from three villages and 20 officials from institutions engaged in agripreneurshipdevelopment in the area (three from all seven agencies) formed the sample size of the study. Farmers taking upentrepreneurial activities generally faced the problems in marketing of their products. Well developed effective linkagesamong all the stakeholders resulted in higher profits for producers and consolidated production sites for marketing andsupply chain agencies. Several institutions engaged in agripreneurship development with respective strengths were foundeffective in synergizing actions and impacts by organizing interaction meets and focus group discussions to arrive atcommon programmes and activities in a collaborative manner.